Borrelia burgdorferi BBA74, a Periplasmic Protein Associated with the Outer Membrane, Lacks Porin-Like Properties - Mulay, Vishwaroop (American Society for Microbiology, 2007)
The outer membrane of Borrelia burgdorferi, the causative agent of Lyme disease, contains very few integral membrane proteins, in contrast to other gram-negative bacteria. BBA74, a Borrelia burgdorferi plasmid-encoded protein, was proposed to be an integral outer membrane protein with putative porin function and designated as a 28-kDa outer membrane-spanning porin (Oms28). In this study, the biophysical properties of BBA74 and its subcellular localization were investigated. BBA74 is posttranslationally modified by signal peptidase I cleavage to a mature 25-kDa protein. The secondary structure of BBA74 as determined by circular dichroism spectroscopy consists of at least 78% α-helix with little β-sheet structure. BBA74 in intact B. burgdorferi cells was insensitive to proteinase K digestion, and indirect immunofluorescence microscopy showed that BBA74 was not exposed on the cell surface. Triton X-114 extraction of outer membrane vesicle preparations indicated that BBA74 is not an integral membrane protein. Taken together, the data indicate that BBA74 is a periplasmic, outer membrane-associated protein that lacks properties typically associated with porins.